A 2D silicon detector array for quality assurance in small field dosimetry: DUO. Issue 2 (2nd February 2017) - Shukaili, Khalsa Al; Petasecca, Marco; Newall, Matthew; Espinoza, Anthony; Perevertaylo, Vladimir L.; Corde, Stéphanie; Lerch, Michael; Rosenfeld, Anatoly B.
Abstract : Purpose: Nowadays, there are many different applications that use small fields in radiotherapy treatments. The dosimetry of small radiation fields is not trivial due to the problems associated with lateral disequilibrium and source occlusion and requires reliable quality assurance (QA). Ideally such a QA tool should provide high spatial resolution, minimal beam perturbation and real time fast measurements. Many different types of silicon diode arrays are used for QA in radiotherapy; however, their application in small filed dosimetry is limited, in part, due to a lack of spatial resolution. The Center of Medical Radiation Physics (CMRP) has developed a new generation of a monolithic silicon diode array detector that will be useful for small field dosimetry in SRS/SRT. The objective of this study is to characterize a monolithic silicon diode array designed for dosimetry QA in SRS/SRT named DUO that is arranged as two orthogonal 1D arrays with 0.2 mm pitch. Methods: DUO is two orthogonal 1D silicon detector arrays in a monolithic crystal. Each orthogonal array contains 253 small pixels with size 0.04 × 0.8 mm 2 and three central pixels are with a size of 0.18 × 0.18 mm 2 each. The detector pitch is 0.2 mm and total active area is 52 × 52 mm 2 . The response of the DUO silicon detector was characterized in terms of dose per pulse, percentage depth dose, and spatial resolution in a radiation field incorporating high gradients. Beam profile of small fields and output factors measured on a Varian 2100EX LINAC in a 6 MV radiation fields of square dimensions and sized from 0.5 × 0.5 cm 2 to 5 × 5 cm 2 . The DUO response was compared under the same conditions with EBT3 films and an ionization chamber. Results: The DUO detector shows a dose per pulse dependence of 5% for a range of dose rates from 2.7 × 10 −4 to 1.2 × 10 −4 Gy/pulse and 23% when the rate is further reduced to 2.8 × 10 −5 Gy/pulse. The percentage depth dose measured to 25 cm depth in solid water phantom beyond the surface and for a field size of 10 × 10 cm 2 agrees with that measured using a Markus IC within 1.5%. The beam profiles in both X and Y orthogonal directions showed a good match with EBT3 film, where the FWHM agreed within 1% and penumbra widths within 0.5 mm. The effect of an air gap above the DUO detector has also been studied. The output factor for field sizes ranging from 0.5 × 0.5 cm 2 to 5 × 5 cm 2 measured by the DUO detector with a 0.5 mm air gap above silicon surface agrees with EBT3 film and MO S kin detectors within 1.8%. Conclusions: The CMRP's monolithic silicon detector array, DUO, is suitable for SRS/SRT dosimetry and QA because of its very high spatial resolution (0.2 mm) and real time operation.